Potential Cosmeceuticals from Marine Constituents - Vigneshwaran L.V; Ann Mary Shaju (Journal of Medical Genetics and Clinical Biology, 2024)
Cosmetic pharmaceuticals, or cosmetic goods with drug-like qualities, are the most recent innovation in the pharmaceutical industry. Klingman coined the term "cosmeceuticals. "There are many, and they are very different, marine resources. As a result, marine components have a variety of possible applications in the cosmetics industry, including as active ingredients, excipients, and additives. Some of the active marine sources used to create cosmeceuticals include sea weeds, marine fish, phytoplanktons, sponges, corals, sea mammals, fungi, bacteria, and mollusks. Cosmetics made from marine resources provide a variety of advantages, such as antioxidant activity, skin whitening, moisturising, de-pigmentation, and anti-aging. The market is flooded with cosmeceuticals that contain marine ingredients. This review focuses on the potential of marine components, a subject that has drawn academics' interest in recent years.